Estimating the Expected Cost of Equity Capital Using Consensus Forecasts - Günther Gebhardt; Holger Daske; Stefan Klein (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2004)
In this study, we develop a technique for estimating a firm's expected cost of equity capital derived from analyst consensus forecasts and stock prices. Building on the work of Gebhardt/Lee/-Swaminathan (2001) and Easton/Taylor/Shroff/Sougiannis (2002), our approach allows daily estimation, using only publicly available information at that date. We then estimate the expected cost of equity capital at the market, industry and individual firm level using historical German data from 1989-2002 and examine firm characteristics which are systematically related to these estimates. Finally, we demonstrate the applicability of the concept in a contemporary case study for DaimlerChrysler and the European automobile industry.
urn:nbn:de:hebis:30-17728
Keywords: 330; Eigenkapital; Kapitalkosten; Finanzanalyse; Börsenkurs; Prognose; Schätzung; Theorie; Deutschland